Insights into the role of dopamine in olfactory learning behavior of honeybee: DOI : 10.48129/kjs.15071 - Raza, Muhammad Fahad; Zhiguo Li; Hongyi Nie; Songkun Su (Kuwait Journal of Science, 2022)
One of the brain's primary functions is remembering and learning information related to food and odour. Since biogenic amines were discovered in invertebrates and vertebrate, dopamine is considered a key modulator and neurotransmitter in honeybees' olfactory learning. Dopamine (DA) is significant in rewarding prediction, learning, invigorating social behavior, and motivation. Here we examined the effect of dopamine in the olfactory learning behavior of honeybees. We used the same age (14-days old) honeybees, Apis mellifera and Apis cerana to evaluate the proboscis extension response and characterized brain dopamine's effect on olfactory learning behavior. Both species were individually trained by performing three learning trials with sucrose solution and odor 1-Hexanol. High-performance liquid chromatography (HPLC) determined the brain dopamine level using electrochemical detection. Our findings showed that Apis mellifera learned better and had higher brain dopamine levels than Apis cerana. Thus, we show that dopamine acts as an essential neurotransmitter and modulator of motivation and influences honeybee cognition.